1986
DOI: 10.1002/jcu.1870140205
|View full text |Cite
|
Sign up to set email alerts
|

Fetal thigh circumference: A critical evaluation of its relationship to menstrual age

Abstract: To provide standards for evaluating fetal thigh circumference measurements obtained with ultrasound, a study of the growth of this parameter during pregnancy was made. Because of possible sampling problems before 22 weeks (menstrual age), this investigation was limited to the 22-40 week time period. Regression analysis indicated that the optimal model (R2 = 88.9%) for describing thigh circumference (ThC) growth was a power function. ThC variability increased with menstrual age, from 1.3 cm at 22 weeks to 3.1 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

1986
1986
2017
2017

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 11 publications
2
9
0
Order By: Relevance
“… The Rossavik model specification for ThC was based on measurements from the first two scans after 22 menstrual weeks2. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… The Rossavik model specification for ThC was based on measurements from the first two scans after 22 menstrual weeks2. …”
Section: Resultsmentioning
confidence: 99%
“…Such aberrations may not be detected if soft tissue abnormalities are the earliest manifestation of pathological growth unless these measurements are sensitive to subtle changes in muscle or fat. Relatively few measurements, such as those from the fetal thigh1–4, abdomen4–7 and cheek8–10 have been evaluated for the prenatal assessment of soft tissue mass.…”
Section: Introductionmentioning
confidence: 99%
“…However, use of the Rossavik model in this case was hampered by the small number (5-8) of data points per fetus that were available and the lack of reliable measurements before 22 weeks. 4 The latter precluded calculation of individual start points that previous studies (unpublished) have indicated give much better results than a single fixed start point. While a start point of 8.0 weeks, menstrual age (time of the appearance of the mesenchymal model of femur), is strongly supported by embryologic data,13 studies with other parameters have shown start point variabilities of + 2 weeks even when the mean start point was in good agreement with embryologic data.5.6 These limitations are probably responsible for the poor estimate of k provided by the longitudinal data set.…”
Section: Modeling Of Thc Growth Curvesmentioning
confidence: 99%
“…The ThC appeared to be linearly related to menstrual age in all four studies. The differences in predicted values can be explained on the basis of methodological differences (particularly the use of Profile shape assumptions in late pregnancy when crowding and decreases in fluid cause significant distortions in profile shape).The normal range (±2D) reported in the three previous studies was 1.71 cm (Jeanty et all, 2.5 cm (Vintzileos et al) (4, 5)and 1.3-3.1 cm (Deter et al) (1). Differences in measurement procedures and variability assessment can easily account for such differences in the normal range.…”
Section: Discussionmentioning
confidence: 94%